Students’ perceptions about the importance of Group Study in the tertiary educational institutions of Bangladesh - Rahman, Md. Anisur (Assyfa Learning Journal, 2025)
The main objective of the study is to focus on Students’ perceptions about the importance of Group Study in tertiary educational institutions of Bangladesh, suitable for students’ academic development in the learning and teaching system. The group study is one of the most recent ideas to develop students’ academic development. The study will also focus on the demand for group study and the challenges of implementing the process in tertiary educational institutions. It is a qualitative and quantitative research study. If it is applied in a proper and constructive way, it will help students to learn a lesson effectively. To implement the process, some issues and action plans should be considered correctly. The researcher described and introduced The Students’ perceptions about the importance of Group Study in tertiary educational institutions and its impact on students’ academic development, with the help of literature, and data were collected from students at the tertiary level.